2020
DOI: 10.1002/pbc.28495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryotherapy on high‐dose melphalan‐induced oral mucositis in pediatric patients undergoing autologous stem cell transplantation

Abstract: Cryotherapy is a conventional method for preventing melphalan‐induced oral mucositis (OM) in adult patients. We retrospectively examined the clinical benefits of cryotherapy in 41 pediatric patients undergoing autologous stem cell transplantation using a melphalan‐etoposide‐carboplatin regimen. Twenty‐two patients received cryotherapy. The cumulative incidence of grade 3‐4 OM was significantly lower in the cryotherapy group (57.1%) than in the noncryotherapy group (89.5%; P = .041). Multivariate analyses ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…No adverse effects were reported in these two RCTs or the other pediatric studies (Appendix 8). In terms of feasibility, two studies suggested compliance was worse in younger patients, specifically in those younger than 7 years [24,26].…”
Section: Strong Recommendationmentioning
confidence: 99%
“…No adverse effects were reported in these two RCTs or the other pediatric studies (Appendix 8). In terms of feasibility, two studies suggested compliance was worse in younger patients, specifically in those younger than 7 years [24,26].…”
Section: Strong Recommendationmentioning
confidence: 99%
“…Ultimately, 10 SRMAs were found to match the criteria and were included 14 33–41. Among the meta-analyses, 25 RCTs17–19 42–62 were included in the umbrella review. From the included meta-analyses, we excluded primary RCTs without control groups,16 63–66 and those with multicomponent interventions,65 non-randomised designs67 and those without full text 68 Online supplemental table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were published between 1991 and 2019. All studies included both sexes, with two conducted on children53 54 and the rest on adults 17–19 42–52 55–62 66. Included trials were from Sweden,50 53 57 60 Turkey,17 18 44 Italy,19 42 47 USA,45 46 62 Iran,43 58 59 China,61 66 Brazil,51 56 Malaysia,52 Greece,55 Canada,48 Japan54 and Denmark 49.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations